2020
DOI: 10.3390/molecules25194478
|View full text |Cite
|
Sign up to set email alerts
|

Cause, Regulation and Utilization of Dye Aggregation in Dye-Sensitized Solar Cells

Abstract: As an important member of third generation solar cell, dye-sensitized solar cells (DSSCs) have the advantages of being low cost, having an easy fabrication process, utilizing rich raw materials and a high-power conversion efficiency (PCE), prompting nearly three decades as a research hotspot. Recently, increasing the photoelectric conversion efficiency of DSSCs has proven troublesome. Sensitizers, as the most important part, are no longer limited to molecular engineering, and the regulation of dye aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 226 publications
(241 reference statements)
0
36
0
Order By: Relevance
“…At the dawn of photography, for example, it was realized that the active sensitizers for color films were aggregates of cyanine dyes . More recently, self-assembled flexible fluorescent fibers have been developed that look promising in terms of thin-film optoelectronic devices. , With particular significance to our work, we note that the large absorption cross-section of certain molecular aggregates, together with rapid exciton migration, has been applied to enhance fluorescence from a very low concentration of embedded dye or dye adhered to the exterior. , Such behavior could be applied to sensitize certain types of organic solar cells. , We have found that crystals of B-P 1 function as efficient sensitizers for sulfonated aluminum phthalocyanine deposits on the surface, at concentrations where the dopant cannot be detected by absorption spectroscopy and its fluorescence is barely visible on direct excitation. In this case, the dimer acts as an intermediary to transfer excitation energy from the filament to the dopant in much the same way that the Fenna–Mathews–Olsen complex couples natural LHCs to their reaction center …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the dawn of photography, for example, it was realized that the active sensitizers for color films were aggregates of cyanine dyes . More recently, self-assembled flexible fluorescent fibers have been developed that look promising in terms of thin-film optoelectronic devices. , With particular significance to our work, we note that the large absorption cross-section of certain molecular aggregates, together with rapid exciton migration, has been applied to enhance fluorescence from a very low concentration of embedded dye or dye adhered to the exterior. , Such behavior could be applied to sensitize certain types of organic solar cells. , We have found that crystals of B-P 1 function as efficient sensitizers for sulfonated aluminum phthalocyanine deposits on the surface, at concentrations where the dopant cannot be detected by absorption spectroscopy and its fluorescence is barely visible on direct excitation. In this case, the dimer acts as an intermediary to transfer excitation energy from the filament to the dopant in much the same way that the Fenna–Mathews–Olsen complex couples natural LHCs to their reaction center …”
Section: Discussionmentioning
confidence: 91%
“… 106 , 107 Such behavior could be applied to sensitize certain types of organic solar cells. 108 , 109 We have found that crystals of B-P 1 function as efficient sensitizers for sulfonated aluminum phthalocyanine deposits on the surface, at concentrations where the dopant cannot be detected by absorption spectroscopy and its fluorescence is barely visible on direct excitation. In this case, the dimer acts as an intermediary to transfer excitation energy from the filament to the dopant in much the same way that the Fenna–Mathews–Olsen complex couples natural LHCs to their reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…The self-aggregation of dye molecules has many technological as well as biological applications. Such spontaneous self-aggregation of dye molecules affects various physicochemical and biological processes in the system. However, dye aggregation is disadvantageous for the application of dyes in dye-sensitized solar cells, lasers, fluorescence sensing, and so on. , In such cases, the behavior of the dyes needs to be inspected carefully in order to develop appropriate strategies to control the aggregation process in the solution phase. Thus, it is of pivotal importance to study thoroughly various aspects of this process for understanding the possible derogatory effect of dye aggregation for its use as a fluorescent probe in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…This result is remarkable since gas‐phase computations typically overestimate torsions found in the solid state when intermolecular forces tend to planarize π‐conjugated molecules. [ 94 ] Thus, these computations strongly suggest that intramolecular lock is very effective within the whole chalcogen series. Furthermore, the data indicates that backbone distortions from planarity in these molecules occurs only between the central XBT core and the end‐capping DTT, DT, and T units, with torsions varying from 13.5° to 15.9°.…”
Section: Resultsmentioning
confidence: 76%